RP HPLC ANALYSIS FOR COUMARIN CONTENT IN CICHORIUM INTYBUS – AN IMPORTANT MEDICINAL PLANT - DAKSHAYINI AND UJWAL P, (International Journal of Pharma and Bio Sciences, 2014)
Cichorium intybus is a medicinal plant commonly used in traditional medicine to treat various infectious diseases. In the present investigation, coumarin was detected in various extracts. An RP- HPLC procedure suitable for the determination of the considered compounds was also developed. Studies were carried out on analysis of secondary metabolites by RP-HPLC from different parts of C.intybus. HPLC detected the coumarin from C. intybus in various part of the plant and leaf derived callus. The plant parts used for the analysis included leaf, root and leaf derived callus. Among all the plant parts used, leaf derived callus recorded the highest concentration of coumarin at 219.73µg/ml. The study indicated that almost all parts of the plant contain coumarin component.